Funções de pedotransferência do solo: estimativa por radiometria - Dotto, André Carnieletto (2012)
The traditional soil analysis many techniques are used in order to determine the physical and chemical properties of the soil. The radiometry appears as a promising alternative technique in the analysis of soil properties. This technique has demonstrated great potential for identification and quantification of certain properties of the soil. It is a non-destructive and non-polluting tool, with the ability to collect data on large spatial dimensions with relative speed. The radiometry may in cases be simpler than the traditional analysis of the soil and on various occasions, more accurately. The main objective of this study was to determine pedotransfer functions to soil properties based on radiometric data. It was observed that the heterogeneity of the soil decreases the accuracy of the models, however it was possible to construct prediction functions for the content of sand, silt, clay and soil organic matter from the radiometry with a level of prediction models acceptable. Considering that, in the prediction of soil properties using radiometry, there is no reagents spending and less resource invested beyond the analysis time shorter than the traditional analysis, the results were promising.